Target loop antenna prototype with magnetic field reduction method - Assamoi, Claude Daniel; Ouattara, Yelakan Berenger; Youan, Bi Tra Jean Claude; Gnamele, N'tcho Assoukpou Jean; Doumbia, Vafi (International Journal of Electrical and Computer Engineering (IJECE), 2024)
This paper proposes a new large loop antenna with a reduced magnetic field for a near field communication (NFC) target used in a metallic environment. It also defines a fairly clear method for controlling and, more specifically, reducing the magnetic field associated with loop antennas. This antenna consists of a circular winding, inside which we insert a square winding arranged in the shape of a diamond. The particular structure of this antenna shows that it is possible to dissociate the increase in the induced magnetic field, linked to its large size, from the increase in the number of windings. This is made possible by the application of the physical principle of overlapping magnetic fields, which results in partially destructive interference.